Desmontagem cênica: investigação das poéticas do ator em teatro de grupo - Santos, José Raphael Brito dos (2015)
This work is a though concerning disassembly as a way of research about the scenic creation processes, with emphases in the actor s poetics in the group theatre context. The actor s poetics, in the case of this work, comprehend his experiences in the collective creation and/or the collaboration process cooperative nets in which the performance construction is established in group. Disassembly is a practice that began with Latin American theatre groups that would use this procedure in order to present testimonies, tessituras, features and trajectories of a creation process. This research follow the course of the quality aspect with theoretical foundations, interviews and, in some parts, the author uses the first-person narrative to expose his personal experiences. The theoretical analysis was based upon investigations about Theatre in group, Actor in Cooperative Net of Creation and Disassembly, from the previous studies of RosyaneTrotta (2008), André Carreira (2007) and Ileana Diéguez (2009), to name some of them. This document is divided in three chapters: the first one contains a contextualization of the actor creation practices in a group theatre, lightening out conceptual and historical matters. Finally an incitation is presented: How to research the creation processes? The second chapter encloses the scenic disassembly as an investigation procedure about the actor s poetics, and invites the group theatre actress TâniaFarias to narrate her experience in the exercise of unset her performances, contribution that encourage the development of proposals about the topic. The third chapter regards the exercise of written disassembly, in which the author spins his creation path based on his own experiences at the Núcleo de Pesquisas Teatrais Rascunho, (Core of Theatrical Research Rascunho) and shares his creation processes of the following shows: Lullaby; Esperando Godot (Waiting Godot); Primeiro Amor (First Love) and Siameses (Siamese).